Por uma teoria das normas ambientais sob a ótica da natureza como sujeito de direito : quebra de paradigmas - Souza, Roberto Wagner Xavier de (2013)
This research has as its main justification the recent and major debates in the legal or socialnormative area about the recognition of nature as a subject of law, especially with the advent in 2008 of the new Ecuadorian Constitution, which was the first to assign to nature of this feature directly. The research problem sought to clarify the nature, facing the crisis and the new paradigmatic constructions and contemporary auspices, can go through a rereading sociolegal palpable. Thus, the scientific research on screen sought to identify and analyze the perspectives of characterizing and reframe the Nature, as a subject of law. Specifically, it aimed to: i) identify the values socio-legal, ethical and philosophical pertaining to new construction paradigm of Nature as Subject of law, ii) Setting up of scientific activity within the need to perform it with the fulcrum translate their bases and objectives in building a new sense environmental iii) List the legal parameters in standards and international constitutions and laws and regulations and to correlate them with the ideas of deep ecology and ecocentrism iv) analyze the role of the state, guarantor and provider rights, the enforceability of those duties to achieve with regard to the environment compared axiological content of the principles of international environmental law and the Federal Constitution. The research was exploratory and literature by emphasizing the discovery of ideas and insights as well as collecting data in written materials. Concepts and descriptions were evaluated, many of them are not in the normative text, but present in doctrine. Through deductive method-classical dialectic, but also a logical inductive conclusive, was related to the content standards in drawing a parallel study from the perspective and the basic premise ecocentrism and sustainable development as a point of equilibrium relations man - nature. Moreover, the analysis drew upon elements of legal hermeneutics without forgetting the philosophical approach and environmental ethics. The study led to the progressive concatenation and the real connotation in promoting the moral considerability and legal nature, its feasibility and principles that guarantee, given the relationship of multicultural and formative elements of the Brazilian state are not relevantly different from other states, whose already made the transition paradigm